The impact of age generation on wellbeing among homestay guest at Langkawi Island - Jamaluddin, Askiah; Zulkifle, Zuzafina; Zainalaluddin, Zumilah (Human Resource Management Academic Research Society, 2022)
Behaviour of tourists among Generation Y, Generation X, and Baby Boomers is often uncertain while travelling. Tourism well-being is happiness during travelling, which produces a better healthy body (physical) and mind (mental). There is an arising literature body on ecosystem services in a culture that focuses on human well-being, despite that the tourism attachment was underexplored with a few exceptions, such as age categories. This paper aims to analyse the impact of age category on tourism well-being among homestay guests at Langkawi Island. This paper was conducted using a quantitative method, and the data was collected by simple random sampling. The questionnaires were distributed to the homestay owner at the several homestays at Langkawi Island. Then, their homestay guest answered and was the respondent for this study. There are 364 respondents in this study. The Tourism Well-Being (TWB) was measured using eight dimensions: our establishment, services, host provider, price, novelty, hedonism, social value, and satisfaction. This paper found that Generation Y is highest tourism well-being, followed by Generation X. In contrast, the age generation with the lowest tourism well-being is Baby Boomers (BB). This research contributes and gives insight to the Ministry of Tourism, Arts, and Culture (MOTAC) in promoting homestay tourism activities in Langkawi Island.